Technical And Financial Risks Challenging the Adoption of Smart Contracts in Construction (Aintelia Science Notes, 2022)
A smart contract is characterized as computerized transaction procedures that meet contractual constraints such as progress payment, claims, and confidentially while minimizing the need for an intermediary. Smart contracts may be thought of as an effective and different answer to the typically lengthy, complex, and difficult-to-comprehend construction contracts. Construction businesses face several technical and financial risks when using smart contracts. Risks discovered through literature research were communicated to specialists, and their comment was obtained following the study. From a financial and technological aspect, it is recognizable that the incorporation of smart contracts into construction management processes will be risky, according to expert opinions.
Keywords: Smart Contracts; Automated Construction Process; Technical Risks